Explosive particles for repairing rock cracks using ammonia nitrogen, preparation method and repair method
By using ammonia nitrogen to repair explosive particles in rock mass fractures, urea and microorganisms are released through gel film and water-soluble membranes, and calcium carbonate crystals are catalyzed, which solves the problems of poor repair of rock mass fractures and water pollution in the prior art, and achieves efficient crack repair and water purification.
Patent Information
- Application Number
- CN202310589039.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-05-24
AI Technical Summary
The existing rock crack repair technology has problems such as poor compatibility, high cost, high pollution and poor repair results. Especially in the desolation zone environment of the Yangtze River Basin, it is difficult to effectively repair cracks and purify water bodies.
An explosive particle that uses ammonia nitrogen to repair rock fractures is used. The particle consists of a gel film and a water-soluble film, which encapsulates urea and microorganisms. By reacting with ammonium ions in water, the microorganisms catalyze the production of carbonate ions, forming calcium carbonate crystals, which attach to the crack walls, and achieves crack repair and water purification.
This method can effectively repair rock cracks, improve the mechanical properties and durability of the cracks, and at the same time purify the water body, reduce pollution, and achieve green and environmentally friendly repair results.
Smart Images

Figure CN116621607B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rock mass crack repairing, in particular to explosive particles for repairing rock mass cracks by utilizing ammonia nitrogen. Background Art
[0002] The Yangtze River Basin, as the world's third largest river and China's largest river, has brought us extremely rich natural resources. However, since the construction of the Three Gorges Project, the ecological and environmental problems it has caused have always been a concern for the world. Given that the Three Gorges Project adopts the "storing clear water and discharging turbid water" operation mode, that is, the operating water level in winter (dry season) is 145m, and the operating water level in summer (flood season) is 175m, this will form a drawdown zone with a maximum water level difference of 30m in the reservoir area along the river.
[0003] Due to the slow flow rate in the reservoir area, the nitrogen and phosphorus carried by the surface runoff have led to an increasing degree of eutrophication in the reservoir area. At the same time, the rise and fall of water levels and complex geological conditions have caused cracks in the rock mass in the drawdown zone on both sides of the bank, reducing the mechanical and durability properties of the reservoir bank slopes. If not repaired in time, there will be a major safety hazard. Therefore, in order to maintain the ecological environment along the coast, the cracks need to be repaired in a timely manner.
[0004] Traditional crack repair generally uses polymer ultrafine cement, epoxy resin materials, high molecular grouting materials, etc., which have disadvantages such as poor compatibility, high cost, and high pollution during use. For the Yangtze River Basin, this type of slurry will cause certain pollution to the water body, so a new green repair method is needed. Microbial Induced Carbonate Precipitation (MICP) is an eco-friendly energy-saving technology with the advantages of low energy consumption, many types, and environmental friendliness. It has been widely used in crack repair in geotechnical engineering, and the product of microbial mineralization is mainly calcium carbonate, which has good stability and durability, good compatibility with the matrix material, and no pollution to the environment. Its mechanism of action is to add urea, calcium source and nutrients to the microbial bacterial solution, rely on the metabolism of the microorganisms themselves, and urease catalyzes the hydrolysis of urea to produce CO3 2- and NH4 + , in alkaline environment CO3 2- Able to interact with surrounding Ca 2+ Combined into CaCO3 crystal precipitation. However, most of the current methods using this principle are to inject microorganisms, urea and calcium sources in sequence to induce microbial calcification. It is difficult to control its reaction in the natural environment, and the natural environment of the repair object is not fully considered, resulting in poor repair effects. Summary of the invention
[0005] The purpose of the present invention is to provide an explosive particle, a preparation method and a repair method for repairing rock cracks using ammonia nitrogen, so as to solve the problems existing in the above-mentioned prior art, realize water purification and crack repair, and ensure the crack repair effect.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] The invention provides explosive particles for repairing rock cracks by using ammonia nitrogen. The explosive particles comprise a gel film and a water-soluble film wrapped outside the gel film. The raw materials of the gel film comprise the following components: modified bentonite, zeolite powder, hydrophilic titanium dioxide, sodium carboxymethyl cellulose solution and agarose solution. The water-soluble film is a polyvinyl alcohol film. Urea is wrapped in the gel film. Nutrients and microorganisms with urease in the body are arranged between the gel film and the water-soluble film. The gel film can adsorb and react with ammonium ions in water. After reacting with the ammonium ions, the gel film will rupture and release the urea therein.
[0008] Preferably, the microorganisms include Bacillus sphaericus and Sporosarcina pasteurianus.
[0009] Preferably, the nutritional substance comprises yeast extract.
[0010] The present invention also provides a method for preparing the above-mentioned explosive particles for repairing rock cracks using ammonia nitrogen, comprising the following steps:
[0011] (1) mixing and stirring the modified expanded soil, zeolite and hydrophilic titanium dioxide to obtain inorganic composite nanoparticles; weighing sodium carboxymethyl cellulose and dissolving it in pure water to obtain a sodium carboxymethyl cellulose solution, then adding the composite nanoparticles to the above solution, stirring thoroughly to obtain an inorganic doped sodium carboxymethyl cellulose solution;
[0012] (2) adding agarose powder to pure water under constant temperature stirring at 80-85° C. to obtain an agarose solution, and slowly adding the inorganic doped sodium carboxymethyl cellulose solution after the solution becomes transparent, accelerating the stirring to form a hydrogel after cooling;
[0013] (3) wrapping urea with the hydrogel and drying at room temperature to obtain a xerogel;
[0014] (4) adding a dry gel and spore powder wrapped with urea to a yeast extract, wherein the spore powder is a spore powder of a microorganism with urease in its body, degassed and mixed, and then injected into a chamber consisting of two glass plates, wherein the two glass plates are separated by a silicone gasket; injecting a polyvinyl alcohol aqueous solution so that it completely covers the mixed solution, and then clamping the glass plates and irradiating them with ultraviolet rays to obtain explosive particles for repairing rock cracks using ammonia nitrogen.
[0015] Preferably, the method for preparing the spore powder comprises the following steps:
[0016] The MBS medium is sterilized, mature spores are transferred as inoculum into the MBS medium, the culture is incubated, the spores are harvested by centrifuging the culture, the supernatant is removed, the spore paste is vacuum dried at room temperature to obtain a dry paste of spores, and then the dry paste of spores is ground to obtain spore powder for encapsulation.
[0017] The present invention also provides a method for repairing rock cracks, which uses the explosive particles for repairing rock cracks using ammonia nitrogen as described above to repair the cracks, and comprises the following steps:
[0018] (1) Spray water with explosive particles onto the rock wall, and the explosive particles flow into the cracks along with the water;
[0019] (2) As the cracks are saturated with explosive particles, the outer water-soluble membrane gradually breaks down over time, releasing the microorganisms inside, which then bind to the calcium source in the crack wall and attach to it;
[0020] (3) As the water level rises, water flows into the cracks. The gel membrane adsorbs and reacts with the ammonium ions in the water. The gel membrane ruptures, releasing the urea inside. The urea produces carbonate ions under the action of microbial urease. The carbonate ions react chemically with the calcium source on the crack wall to produce calcium carbonate crystals, which adhere to the crack wall, thereby purifying the water and repairing the cracks.
[0021] Compared with the prior art, the present invention has achieved the following technical effects:
[0022] The present invention provides explosive particles, preparation methods and repair methods for repairing rock cracks using ammonia nitrogen. After the explosive particles flow into the cracks with water, the outer water-soluble membranes thereof gradually break over time, releasing microorganisms therein. The microorganisms combine with the calcium source in the crack wall and adhere to the crack wall. As the water level rises, water flows into the cracks, the gel membrane adsorbs and reacts with the ammonium ions in the water, the gel membrane breaks, and the urea inside is released. The urea generates carbonate ions under the action of microbial urease. The carbonate ions react chemically with the calcium source on the crack wall to generate calcium carbonate crystals, which adhere to the crack wall, thereby achieving the purpose of purifying the water body and repairing the cracks. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 A schematic diagram of the structure of the explosive particles for repairing rock mass cracks using ammonia nitrogen provided by the present invention;
[0025] Figure 2 A schematic diagram of using explosive particles to repair cracks in the present invention;
[0026] Figure 3 A schematic diagram of spraying a liquid with explosive particles on a ship through a spraying device in the present invention;
[0027] Figure 4 This is a SEM image of the interior of the crack of a sample that has not been treated with microorganisms in the treatment effect measurement test of the present invention;
[0028] Figure 5 This is a SEM image of the interior of the crack of the sample after microbial treatment in the treatment effect measurement test of the present invention;
[0029] In the figure: 1- gel film, 2- water-soluble film, 3- urea, 4- nutrients, 5- microorganisms, 6- cracks, 7- crack walls, 8- calcium carbonate crystals, 9- ship, 10- spraying device. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The purpose of the present invention is to provide an explosive particle, a preparation method and a repair method for repairing rock cracks using ammonia nitrogen, so as to solve the problems existing in the prior art, realize water purification and crack repair, and ensure the crack repair effect.
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0033] like Figure 1-Figure 3 As shown, this embodiment provides an explosive particle for repairing rock cracks using ammonia nitrogen, including a gel film 1 and a water-soluble film 2 wrapped outside the gel film 1, the raw material composition of the gel film 1 includes the following components: modified bentonite, zeolite powder, hydrophilic titanium dioxide, sodium carboxymethyl cellulose solution, agarose solution; the water-soluble film 2 is a polyvinyl alcohol film; urea 3 is wrapped in the gel film 1, and nutrients 4 and microorganisms 5 with urease in the body are provided between the gel film 1 and the water-soluble film 2. The gel film 1 can adsorb and react with ammonium ions in water, and the gel film 1 will rupture and release the urea 3 therein after reacting with the ammonium ions.
[0034] In this embodiment, the water-soluble film 2 is a polyvinyl alcohol film. After the explosive particles are immersed in water, the polyvinyl alcohol film can dissolve over time, thereby releasing the microorganisms 5 therein.
[0035] In this embodiment, the microorganism 5 includes Bacillus sphaericus and Sporosarcina pasteurii. Bacillus sphaericus and Sporosarcina pasteurii have powerful self-repairing functions and are widely used in crack repair. The nutrient 4 includes yeast extract. During production, the microorganism 5 is packaged in the form of spores. At this time, the spores are in a dormant state, and the only nutrient required is yeast extract. When the flood season arrives and a large amount of water is added to the crack 6, the activity of the spores will be activated, and the urease hydrolysis reaction will be carried out to generate calcium carbonate precipitation, thereby repairing the crack 6.
[0036] The above-mentioned method for preparing explosive particles for repairing rock cracks using ammonia nitrogen comprises the following steps:
[0037] (1) A hydrogel is prepared by using the preparation method of a modified hydrogel material with ammonia nitrogen and total phosphorus removal effect disclosed in patent CN 111437796A, and then the hydrogel is wrapped with urea and dried at room temperature to obtain a dry gel; wherein the zeolite powder in the gel film has a strong adsorption effect on ammonia nitrogen in water and is mainly used for the removal of ammonia nitrogen; sodium carboxymethyl cellulose can enhance the mechanical properties of the hydrogel and avoid damage to the hydrogel by strong water flow impact; the modified bentonite is sodium-based bentonite or lanthanum-modified bentonite, and the lanthanum-modified bentonite is mainly used for the removal of phosphorus; thereby, the removal of ammonia nitrogen and phosphorus in water can be achieved, and the purification of water can be achieved;
[0038] (2) the desired microorganisms are cultured into a spore state, spherical Bacillus spores are produced in a liquid minimum basal salt (MBS) medium, the MBS medium is autoclaved at 120°C for 20 minutes before use, mature spores are transferred as inoculum (1%) into the MBS medium, the cultures are incubated (28°C, 100 rpm) for 28 days, and then they are subjected to pasteurization (80°C for 20 minutes, then in ice-cold water for 5 minutes) to minimize vegetative cells, and then the spores are harvested by centrifuging the culture (7000 rpm, 4°C) for 7 minutes, the supernatant is removed, and the spore paste is vacuum dried at room temperature for 3 days, and then the dry spore paste is ground in a cement mill for 5 seconds to obtain spore powder for encapsulation;
[0039] (3) Prepare the outer layer of hydrogel coating material, add the mixture of urea-coated dry gel and spore powder to a certain amount of yeast extract (a nutrient necessary for the survival of spores), deaerate and mix the mixture (5 minutes, 500 rpm), and inject it into a chamber consisting of two glass plates separated by a 1 mm thick silicone gasket. After the materials are mixed, inject a polyvinyl alcohol aqueous solution to completely cover the mixed solution, then clamp the glass plates and irradiate with ultraviolet light for 1 hour. After ultraviolet light irradiation, explosive particles for repairing rock cracks using ammonia nitrogen are obtained.
[0040] A method for repairing rock cracks, using the explosive particles for repairing rock cracks using ammonia nitrogen as described above, comprises the following steps:
[0041] (1) Spraying water with explosive particles onto the rock wall, and the explosive particles flow into the crack 6 along with the water;
[0042] (2) As the crack 6 is saturated with explosive particles, the outer water-soluble film 2 gradually breaks over time, releasing the microorganisms 5 therein, which then combine with the calcium source in the crack wall 7 and adhere to the crack wall 7;
[0043] (3) As the water level rises, water flows into the crack 6. The gel membrane 1 adsorbs and reacts with the ammonium ions in the water. The gel membrane 1 ruptures and releases the urea 3 inside. The urea 3 produces carbonate ions under the action of microbial urease. The carbonate ions react chemically with the calcium source on the crack wall 7 to produce calcium carbonate crystals 8, which adhere to the crack wall 7, thereby achieving the purpose of purifying the water body and repairing the crack.
[0044] In step (1), a boat 9 is used to reach the cliff 11, and then the water containing explosive particles is sprayed onto the cracks 6 on the drawdown zone through a spraying device 10. The water flows into the cracks 6 along the cliff 11, and the explosive particles can reach the deep of the cracks 6 due to their own gravity. Since the outermost water-soluble material of the explosive particles is not affected by pressure, the spraying stage will not cause the explosive particles to be destroyed, and the microorganisms 5 (bacteria) in the internal nutrient solution can survive.
[0045] In step (2), after the bacteria are released, they first combine with the calcium source in the crack wall to fix the bacteria. This is because the positively charged calcium ions can neutralize the negative charge of the bacterial cell wall, making it easier for the bacteria to adsorb on the surface of the negatively charged sand and gravel particles, preventing the microorganisms from being washed away.
[0046] In step (3), taking the Yangtze River waters as an example, as the water level in the Yangtze River waters rises, the drawdown zone is gradually submerged by water, and water continuously flows into the cracks. The gel film that absorbs nitrogen and phosphorus will absorb a large amount of free ammonium ions in the water. The ammonium ions will react with the hydroxides on the gel film, causing the gel film to be destroyed, and the urea inside will be released. The urea will produce carbonate ions under the action of microbial urease. The carbonate ions will immediately react chemically with the calcium source on the crack wall 7 to generate calcium carbonate crystals 8. Since the microorganisms 5 are originally attached to the crack wall 7, the generated calcium carbonate crystals 8 are also attached to the crack wall 7 and are difficult to be carried away by the water flow. They have a certain stability, which makes the effect of repairing the cracks better, achieving the purpose of repairing the cracks, and purifying the water body near the drawdown zone at the same time, preventing the nitrogen and phosphorus content in the water body from exceeding the standard and causing eutrophication of the water body.
[0047] When repairing rock cracks in the drawdown zone on both sides of the Yangtze River, explosive particles are injected into the cracks. The seasonal rainy season in the Yangtze River Basin and the flood discharge and water storage rules of the Three Gorges Reservoir are utilized. As the water level rises and submerges the drawdown zone, the explosive particles react with the ammonium ions in the water and are destroyed. Substances are released to react and form calcium carbonate crystals to precipitate and repair the cracks, achieving the effect of "healing rock with water".
[0048] The present invention provides the following test scheme to simulate the process of microbial treatment of the drawdown zone, and conducts measurement tests to observe the treatment effect of the drawdown zone.
[0049] 1. Production of the drawdown zone model and simulation environment
[0050] Use a 3D contour laser scanner to scan the appearance of the drawdown zone (including cracks) in a certain area of the Yangtze River Basin, and make a mold based on the scanning results; take the sand and soil on site and mix it with a certain water-soil ratio and inject it into the mold. The resulting drawdown zone model is similar to the drawdown zone in the real environment. Use the same method to make multiple models for subsequent test comparisons. Take a square box with a water pipe at the bottom, and simulate the ups and downs of the water level of the Yangtze River during the drought and flood seasons by pumping and injecting water. The original water body of the Yangtze River should be simulated.
[0051] 2. Microbial control test
[0052] A liquid containing mixed explosive particles is sprayed into the crack of one of the models using a micro-nozzle, and the model is then placed vertically (the direction of the crack extension is perpendicular to the desktop) in a square box. As time goes by, the outer water-soluble film 2 disappears, releasing microorganisms that first react with the calcium source in the crack wall to fix the bacteria; after a period of time, water is injected into the box, and the inner gel film 1 absorbs a large amount of free ammonium ions through the action of substances such as zeolite, reacts with hydroxide to break it and release urea. The urease (urea amide hydrolase-EC3.5.1.5) contained in the microorganism catalyzes the hydrolysis of urea into ammonia and carbon dioxide. The hydrolysis of one urea molecule results in the release of two ammonia molecules and one carbon dioxide molecule. The enzymatic hydrolysis of urea is generally described as:
[0053]
[0054] The ammonia released by urea hydrolysis causes an increase in the pH of the surrounding medium, where the supplemented mineral ions (Ca 2+ and CO3 2- ) can precipitate CaCO3. White fine crystals can be observed in the cracks. Four microbial treated model samples were made in sequence, and the remaining untreated models in the first step formed four control test groups.
[0055] 3. Governance effect measurement test
[0056] Crystallization effect:
[0057] The first group of test samples were observed using SEM (scanning electron microscope) to observe the surface morphology and microstructure in the cracks, such as Figure 4 The following is a SEM image of the crack inside the sample without microbial treatment. Figure 5 This is the SEM image of the inside of the crack of the sample after microbial treatment. It can be confirmed that there is a good crystallization effect inside the crack of the sample after microbial treatment.
[0058] The second group of samples were tested for water permeability. The samples were sealed with a rubber sleeve and placed horizontally in a container smaller than the sample. Water was then slowly added to measure the mass of water that passed through the sample. -12 m -2 Down to 29×10 -12 m -2 , it can be clearly observed that the water permeability of the samples after microbial treatment is lower than that of the untreated samples.
[0059] The third group of samples was tested for shear strength using a direct shear test. The control samples were placed in a direct shear tester and slowly loaded until the samples were damaged. The untreated samples and the repaired samples were subjected to shear tests under normal stresses of 50kPa, 100kPa, and 150kPa, respectively, to obtain the relationship between the peak shear stress and the normal stress. Based on the relationship between the two, the changes in cohesion and internal friction angle before and after repair were obtained. The cohesion ranged from 128.64 to 142.72kPa, which was about 25 times that before repair. The average shear strength was 0.28MPa, which was 4-5 times that before repair.
[0060] Adsorption effect of ammonia nitrogen and phosphorus:
[0061] The ammonia nitrogen and total phosphorus content in the water before and after the experiment were tested to evaluate the adsorption effect of the blasting particles. First, the original water was tested, and the initial ammonia nitrogen content was 4.10 mg / L and the total phosphorus content was 0.82 mg / L. During the five days of the experiment, the water was tested once a day to obtain dynamic observation data, as shown in Table 1.
[0062] Table 1 Ammonia nitrogen and total phosphorus content test values
[0063] time Total phosphorus content (mg / l) Ammonia nitrogen content (mg / l) Initial Value 0.82 4.1 Day 1 0.81 4.02 the next day 0.78 3.87 Day 3 0.72 3.52 Day 4 0.63 3 Day 5 0.58 2.77
[0064] Using an ammonia nitrogen detector, ammonia nitrogen in the form of free ammonia or ammonium ions reacts with an alkaline solution of potassium iodide and mercuric iodide to form a light reddish brown complex, whose chromaticity is proportional to the ammonia nitrogen content. A rough measurement can directly observe whether there is a difference in the amount of light red complex before and after the experiment. The quantitative observation effect can be obtained by measuring the absorbance of the complex at a wavelength of 420nm, which is proportional to the ammonia nitrogen content. The absorbance is measured at a wavelength of 420nm to calculate its content. The absorbance before the test was 0.02009A, corresponding to an ammonia nitrogen content of 4.1mg / L. The absorbance after the test was 0.010913A, corresponding to an ammonia nitrogen content of 2.77mg / L. Therefore, according to the absorbance values of the complex before and after the experiment measured by the instrument, part of the ammonia nitrogen was adsorbed.
[0065] The total phosphorus content of the water sample was measured to be 0.82 mg / L before the test. After microbial remediation, the phosphorus content of the water sample was tested again and the total phosphorus content finally dropped to 0.58 mg / L after five days, indicating that the phosphorus in the water body was absorbed.
[0066] The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only used to help understand the method and core ideas of the present invention. At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. An explosive particle for repairing rock cracks using ammonia nitrogen, characterized in that: The invention comprises a gel film and a water-soluble film wrapped outside the gel film. The raw materials of the gel film comprise the following components: modified bentonite, zeolite powder, hydrophilic titanium dioxide, sodium carboxymethyl cellulose solution and agarose solution. The modified bentonite, zeolite powder and hydrophilic titanium dioxide form composite nanoparticles, and the mass ratio of the modified bentonite, zeolite powder and hydrophilic titanium dioxide is 1-5:4-8:
1. The mass ratio of the agarose solution, the sodium carboxymethyl cellulose solution and the composite nanoparticles is 5:0.8-1.5:0.05-0.
2. The modified bentonite is sodium-based bentonite or lanthanum-modified bentonite, and the water-soluble film is a polyvinyl alcohol film. Urea is wrapped in the gel film, and nutrients and microorganisms with urease in the body are arranged between the gel film and the water-soluble film. The gel film can adsorb and react with ammonium ions in water, and the gel film will break and release the urea therein after reacting with the ammonium ions.
2. The explosive particles for repairing rock cracks using ammonia nitrogen according to claim 1 are characterized in that: The microorganisms include Bacillus sphaericus and Sporosarcina pasteurianus.
3. The explosive particles for repairing rock cracks using ammonia nitrogen according to claim 1 are characterized in that: The nutritional substance includes yeast extract.
4. A method for preparing explosive particles for repairing rock cracks using ammonia nitrogen as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing and stirring the modified expanded soil, zeolite and hydrophilic titanium dioxide to obtain inorganic composite nanoparticles; weighing sodium carboxymethyl cellulose and dissolving it in pure water to obtain a sodium carboxymethyl cellulose solution, then adding the composite nanoparticles to the above solution, stirring thoroughly to obtain an inorganic doped sodium carboxymethyl cellulose solution; (2) adding agarose powder to pure water under constant temperature stirring at 80-85° C. to obtain an agarose solution, and slowly adding the inorganic doped sodium carboxymethyl cellulose solution after the solution becomes transparent, accelerating the stirring to form a hydrogel after cooling; (3) wrapping urea with the hydrogel and drying at room temperature to obtain a xerogel; (4) adding a dry gel and spore powder wrapped with urea to a yeast extract, wherein the spore powder is a spore powder of a microorganism with urease in its body, degassed and mixed, and then injected into a chamber consisting of two glass plates, wherein the two glass plates are separated by a silicone gasket; injecting a polyvinyl alcohol aqueous solution so that it completely covers the mixed solution, and then clamping the glass plates and irradiating them with ultraviolet rays to obtain explosive particles for repairing rock cracks using ammonia nitrogen.
5. The preparation method according to claim 4, characterized in that: The preparation method of the spore powder comprises the following steps: The MBS medium is sterilized, mature spores are transferred as inoculum into the MBS medium, the culture is incubated, the spores are harvested by centrifuging the culture, the supernatant is removed, the spore paste is vacuum dried at room temperature to obtain a dry paste of spores, and then the dry paste of spores is ground to obtain spore powder for encapsulation.
6. A method for repairing rock cracks, characterized in that: The method of repairing rock mass cracks by using explosive particles for repairing rock mass cracks using ammonia nitrogen according to any one of claims 1 to 4 comprises the following steps: (1) Spray water with explosive particles onto the rock wall, and the explosive particles flow into the cracks along with the water; (2) As the cracks are saturated with explosive particles, the outer water-soluble membrane gradually breaks down over time, releasing the microorganisms inside, which then bind to the calcium source in the crack wall and attach to it; (3) As the water level rises, water flows into the cracks. The gel membrane adsorbs and reacts with the ammonium ions in the water. The gel membrane ruptures, releasing the urea inside. The urea produces carbonate ions under the action of microbial urease. The carbonate ions react chemically with the calcium source on the crack wall to produce calcium carbonate crystals, which adhere to the crack wall, thereby purifying the water and repairing the cracks.
Citation Information
Patent Citations
Microbial self-repairing concrete and preparation method thereof
CN112500074A
Concrete crack self-repairing material based on microorganism synergistic mineralization and application
CN113121145A